Collectie Océ-van der Grinten : Jonge kunst 1990-1996. - van Grevenstein, Alexander; Lucker, Louis; Pontzen, Rutger; Bonnefantenmuseum, Maastricht ([S.l.] : Stichting Océ Kunstbezit, 1996)
Kelderman, Lize ; Jonker, Kees ; Molenaar, Jurriaan ; Ebling Koning, Koen ; ter Heijne, Mathilde ; Broek, Hans ; Lenssen, Theo ; Suermondt, Robert ; Hermans, Benoît ; Doorduin, Marcel ; de Haan, Annemiek ; van den Bosch, Matthijs ; Nijeboer, Evelien ; de Moor, Lara ; Herzog, Petra ; Drummen, Suzan ; Klein, Carla ; Sijbring, Riek ; Vermeule, Koen ; et al.
Gelijknamige tentoonstelling in Bonnefantenmuseum, Maastricht, 12 mei - 8 september 1996
kunstcatalogus